2000
DOI: 10.1128/mcb.20.6.1947-1955.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Est1 Subunit of Yeast Telomerase Binds the Tlc1 Telomerase RNA

Abstract: Est1 is a component of yeast telomerase, and est1 mutants have senescence and telomere loss phenotypes. The exact function of Est1 is not known, and it is not homologous to components of other telomerases. We previously showed that Est1 protein coimmunoprecipitates with Tlc1 (the telomerase RNA) as well as with telomerase activity. Est1 has homology to Ebs1, an uncharacterized yeast open reading frame product, including homology to a putative RNA recognition motif (RRM) of Ebs1. Deletion of EBS1 results in sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 44 publications
5
91
0
Order By: Relevance
“…EST2 and TLC1 encode the reverse transcriptase catalytic protein subunit and the templating RNA, respectively 9,11,12 . In addition, the protein encoded by EST1 is associated with the RNA component of telomerase, TLC1 (refs [13][14][15][16]. Other accessory factors, such as Cdc13, are required for the in vivo action of telomerase.…”
mentioning
confidence: 99%
“…EST2 and TLC1 encode the reverse transcriptase catalytic protein subunit and the templating RNA, respectively 9,11,12 . In addition, the protein encoded by EST1 is associated with the RNA component of telomerase, TLC1 (refs [13][14][15][16]. Other accessory factors, such as Cdc13, are required for the in vivo action of telomerase.…”
mentioning
confidence: 99%
“…Est1p has been reported to contain a region with weak sequence homology with the consensus RRM, and mutants in this region do not complement an est1⌬ strain and no longer co-immunoprecipitate TLC1 RNA (Zhou et al 2000). The function of this region is not entirely clear, however, because a subsequent report showed that Est1p containing a deletion in this region was still able to partially co-immunoprecipitate the RNA (Evans and Lundblad 2002).…”
Section: How Might Est1p Interact With the Bulged Stem?mentioning
confidence: 91%
“…This interaction occurs independently of most of the RNA, as a TLC1-535-707 fragment is sufficient for coimmunoprecipitation of Est1p. Co-immunoprecipitation of the telomerase RNA and Est1p has been shown to be independent of Est2p (Zhou et al 2000), so it is unlikely that Est2p mediates this interaction. Furthermore, coimmunoprecipitation of the RNA with Est3p is dependent on the presence of Est2p (Hughes et al 2000); therefore, Est1p interaction with the RNA should be independent of Est3p as well.…”
Section: Interaction With Est1p Is Dependent On An Intact Bulged Stemmentioning
confidence: 99%
“…The TDR included only a few genes previously implicated in telomere function. Three of these were down-regulated when telomeres were shortest: RAP1, a central negative regulator of telomere length (19); EBS1, a gene that contains an RRM RNA recognition motif and is also homologous to the telomerase component EST1 (20); and TBF1, which encodes a DNA-binding protein (21). Rap1p and its associated proteins regulate access of telomerase to the telomere in a lengthdependent manner (19); thus, RAP1 down-regulation could be an adaptive response to shortened telomeres.…”
Section: Genome-wide Response To Deletion Of Telomerasementioning
confidence: 99%